Diffuse post-traumatic calcification of the anterior longitudinal ligamentum of cervical and dorsal spine - C.U. Manzini; V. Spina; M.T. Mascia; R. Magistro; G. Carpenito; C. Ferri (PAGEPress Publications, 2004)
Among the different conditions causing flogosis and calcification/ossification of the soft tissues of the spinal cord, single or recurrent traumatic events are included. Within the international literature, the involvement of the posterior longitudinal ligament, following spinal cord injuries is frequently reported, especially in the elders. The Authors describe here an uncommon calcification/ossification of the anterior longitudinal ligament occurred after a double traumatic event in a young man, followed clinically and radiologically for a long-term period. On the basis of clinical, bioumoral and radiological findings, the differential diagnosis with other possible aetiologies, especially DISH (Diffuse idiopathic skeletal hyperostosis) and ankylosing spondylitis, is discussed.